Cartoon As Instructional Method in Teaching Descriptive Text Writing - Amrizal, Amrizal (Ahmad Dahlan Journal of English Studies, 2015)
Writing is a part of four language skills that the students have to be comprehended. In fact,Â  many students are unable to do so because they believe that learning to write is difficult. Several resons exist for this dilemma. One is that grammatical rules for the English language are much different than those of Bahasa Indonesia. Second, students typically prossess a limit vocabulary. Third, students do not have much motivation to write English text. One of potential solution to increase writing skills for writing (descriptive text) using cartoon media. In applying cartoon media, the teacher asks students to describe items based on a cartoon, and then after the students have described things such as colour and form. They are asked to compare stories to see which ones are closest to real story and retell the stories what student write. Using this method helps for several reasons. First, the method attacts studentsâ attention. Second, visual material have been shown to be helpful because they are engaging.